Creating new spheres of experience in the transition to a nursing home - Zittoun, Tania; Grossen Peretti, Michèle; Tarrago Salamin, Fabienne (My University, 2020)
Drawing on sociocultural psychology, we sketch out a new approach to the development of persons in old age, especially when they enter a nursing home and start a new life there. Based on the results of a qualitative case study of a nursing home in Switzerland, we examine both the social and material conditions of living in a nursing home, and look at how they are linked to residents' subjective experience and sense of self-continuity (Erikson & Erikson, 1998). Data collection includes, first, documentation of the institutional and organizational background of the nursing home; second, observations of the institutional life and interviews with the manager, staff, and some of the residents' family members, in order to find out how the nursing home operated on a daily basis; third, interviews with the residents themselves, in order to understand their subjective experience and their use of time and space. Analysis showed that the residents displayed creativity in transforming the given environment into new personal spheres of experience. They also created distal spheres of experience, through the use of various symbolic resources and objects. In so doing, they called up vivid memories of their past, as well as imaginary explorations of alternative presents and possible futures. These imaginary explorations supported their personal continuity, as well as their engagement and imagination. We highlight the theoretical and practical implications of our findings.
Keywords: Nursing home Transition Learning Creativity Materiality Symbolic resources